PKP-015 Optimal dose regimen of antibiotics against methicillin-resistant Staphylococcus aureus in critically ill patients undergoing continuous venovenous hemodiafiltration. (24th February 2014) - Carcelero, E; Soy, D; Guerrero, L; Castro, P; Poch, E; Fernández, J; Badia, JM; Nicolas, JM
Abstract : Background: Methicillin-resistant Staphylococcus aureus (MRSA) is usually involved in nosocomial infections. Acute Kidney Injury (AKI) and a state of high haemodynamic instability are common in ICU patients, thus continuous venovenous haemodiafiltration (CVVHDF) is gaining significance in this setting. Timely and adequate antibiotics are needed according to resistance data (EUCAST-2013). To date, vancomycin (VAN), linezolid (LNZ) and daptomycin (DAP) doses during CVVHDF have not been fully established. Purpose: To evaluate the pharmacokinetics (PK) of vancomycin, linezolid and daptomycin in critically ill patients undergoing CVVHDF to further optimise antibiotic dose regimens. Materials and methods: Prospective, one-year PK study in ICU patients with AKI requiring CVVHDF and treated with VAN, LNZ or DAP. Data collected: patient demographics; dosage; CVVHDF characteristics; venous blood samples pre-dose and several times post-dose. Drug concentrations were analysed by HPLC/UV. PK parameters were determined by non-compartmental analysis [elimination half-life (t1/2 ), area under the concentration-time curve (AUC0-τ ), total clearance (CLtot ) and apparent volume of distribution at steady-state (Vss )]. Optimal PK/PD indices (AUC–24 /MIC): VAN >400; LNZ >100; DAP > 600. Results: Fourteen patients (10 VAN: 15 mg/kg/24 h; 2 LNZ: 600 mg/12 h; 2 DAP: 8 mg/kg/48 h) were included in the study. Mean (SD) age: 61.1(14.6) years. Mean (SD) weight: 72.1(13.9) kg. Ten patients were male. CVVHDF was performed at a dialysate flow rate: 0.7–1.5 L/h and ultra-filtration flow rate: 0.7–2 L/h. The blood flow rate ranged from 140 to 200 mL/min. Median [range] t1/2 and Vss were: 18.2 h [6.8–30.9 h] and 1.7 L/kg [0.8–3.1 L/kg]; 6.1 h [4.9–7.4 h] and 0.6 L/kg [0.5–0.7 L/kg]; 24.1 h [19.5–28.7 h] and 0.25 L/kg [0.2–0.3 L/kg], for VAN, LNZ and DAP, respectively. Median [range] CLtot of VAN, LNZ and DAP was 5.2 L/h [2.9–8.3 L/h], 4.45 L/h [3.6–5.3 L/h] and 1.15 L/h [1.1–1.2L/h] respectively. The percentage of total dose removed by CVVHDF was: VAN 40.1%; LNZ 36.5% and DAP 53%. Median [range] VAN, LNZ and DAP AUC–24 was 125.3 mg*h/L [71-–83.8 mg*h/L], 263.5 mg*L/h [214.1-–12.9 mg*h/L] and 468.6 mg*h/L [379.9-–68.6 mg*h/L], respectively. Conclusions: A VAN dose higher than 15 mg/kg/day is required to optimise the PK/PD target. Therapeutic VAN monitoring is strongly recommended in CVVHDF patients. Standard LNZ dose: 600 mg bid is appropriate to optimise the AUC–24 /MIC ratio for susceptible microorganisms. In contrast, a dose of 8 mg/kg/48 h of DAP appears to be insufficient to achieve the PK/PD target. Higher DAP doses would be needed (10-–2 mg/kg/48 h). No conflict of interest.